Phenomenology and ontology in the thought of Edmund Husserl - Andrei-Bogdan MIȘCOL (Studia Universitatis Babeș-Bolyai. Philosophia, 2024)
In this paper I examine Husserlian phenomenology and its relations with a possible ontology that the great German philosopher cultivated as a project, an undeclared ontology. Husserl's expression of the “ultimately and truly absolute” as a “primeval source” is not explained by a declared ontology and the concept of the “continuum” is in the same situation.